A high precision record of mid-late Holocene sea-level events from emergent coral pavements in the Houtman Abrolhos Islands, southwest Australia - Collins, Lindsay; Zhao, J.; Freeman, H. (2005)
Early work on sea-levels in southwest Australia claimed to recognise a Holocene sea-level highstand which was not seen in better known sea-level records elsewhere at the time, and more recent work has confirmed that a mid Holocene highstand occurred about 6 ky ago. As new data on oscillating sea-levels from the region have recently been published, a high continuity, precisely dated and accurately surveyed record was obtained from emergent coral pavements in the leeward Houtman Abrolhos Islands (Serventy Island), a tectonically stable region from where good quality Holocene sea-level data have been previously obtained from corals. From the mid Holocene highstand close to 7 ky U/Th ago, sea-level declined linearly during the remainder of the Holocene as the carbonate platform prograded leewards. Hydro-isostatic cotrols are probably significant in the record.